METHODOLOGY OF DETERMINING STRESS FORCES AND ANGULAR MOMENTUM THAT AFFECT POWER TAKE-OFF ELEMENT OF WATER ENERGY CONVERTER DURING STORM - Капітанчук, К. І.; Андріїшин M. П. (Science-based technologies, 2019)
Marine energy (also sometimes referred as Global Ocean power) contains enormous energy potential carried by ocean waves, tides, salinity and temperatures differences. This is vast and mostly untapped source of renewable and clean energy that can provide 20,000–80,000 terawatt-hours per year (TWh/y) of electricity (according to year 2007 International Energy Agency annual report on Ocean Energy Systems IEA-OES). When evaluating wave energy as a source of electricity it is important to understand engineering challenges of chosen approach. Common flaw of typical wave energy converters designed and currently in use around world is a vulnerability to sudden changes in environment conditions during storms that could greatly differ from conditions used for calculations. Problem of destructive influence of waves during sudden changes in wind force and direction is solved by flooding of a power take-off element and a platform to the depth where parameters of waves met calculation values, without station operational mode change. Thus consumers stably receive the declared quantity of the electric power. Important issue is to choose correct materials for parts of wave energy converter, especially power take-off element, due to increased forces applied during storms. Environmental concerns of marine energy developments are to consider influence of engineered structure on ocean fauna and flora therefore: - wave converters have to take away energy from ecosystem without disrupting usual nature processes; - consider risk of marine mammal, fish and plants being struck by energy converter’s turbine blades; physical presence of marine energy project to alter the behavior of ecosystem flora and fauna by attraction or avoidance; - potential effect on nearfield and farfield marine environment and processes as sediment transport or water quality. Suggested method allows to create water energy converter according to water area seasonal conditions and atmospheric environmental conditions. Using this method will determine forces that affect power take-off element. After calculations are finished the information about velocity diagrams and stress-strain curves along power take-off element radius will allow to engineer the form of power take-off element and choose corresponding materials for certain parts.